Production of hair sheep under grazing conditions in north-eastern Mexico - Quintanilla Medina, Jairo Jeú (2018)
The objective of the study was to evaluate the effect of genotype, sex, twins and year of birth on the productive behavior of purebred hair lambs (Blackbelly, Katahdin and Pelibuey) and crosses (Blackbelly x Dorper-Pelibuey) in a production system with intensive grazing in the area of Güémez, Tamaulipas, Mexico. Data from 290 lambings from four lambing seasons were analyzed with a linear model. Birth weight was greater in Katahdin (3.75 kg) and in single lambing (3.74 kg) as compared to twin lambing, while the sex of the lamb did not show significant difference. The body weight gain at weaning was greater in the Blackbelly x Dorper-Pelibuey lambs (0.217 kg), as well as the weaning weight (16.65 kg).